The potential of kaolinite as a landfill liner material - Aimi Jehan, Hamzah (2010)
Leachate virtually is one of the problems in landfill system. The landfill liner with different types has widely been used in modern landfill to overcome the problems. Bentonite and Kaolinite are a clay mineral that can be used as landfill liner material. Bentonite is better to be a landfill liner because it have the lowest permeability compare to Kaolinite. But Bentonite has the highest swell-shrink potential because of the highest plasticity index that can be determine from Atterberg Limit. Kaolinite helps to reduce the permeability and swell-shrink potential of Bentonite when they are mixed together. Seven different ratios are tested to determine the effectiveness ratio of Bentonite and Kaolinite which are 100:0, 40:60, 30:70, 20:80, 10:90 and 0:100. The tests involved are Atterberg limits, Specific Gravity, Permeability test and Oedometer test. Too much Bentonite will cause a higher swell-shrink potential but low permeability while too much Kaolinite causes a lower swell-shrink potential but high permeability. Oedometer test is conducted to determine the- coefficient of consolidation in order to determine how much time needed to complete the consolidation settlement. From the results, the permeability for landfill liner are obtained where Bentonite is impermeable than Kaolinite and after it mixed the ratios become more impermeable. The ratio Bentonite:Kaolinite, 30:70 is chose to be an effective ratio to be used as a landfill liner material. This because of it low coefficient of permeability and at the same time has a stability of plasticity index and consolidation.